Euthanasia, Abortion, Death Penalty and Religion - The Right to Life and its Limitations International Empirical Research - Ziebertz, Hans-Georg.; Zaccaria, Francesco; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book considers how the termination of life might be accepted in the view of a general obligation to protect life. It features more than 10 papers written by scholars from 14 countries that offer international comparative empirical research. Inside, readers will find case studies from such areas as: India, Chile, Germany, Italy, England, Palestine, Lithuania, Nigeria, and Poland. The papers focus on three limitations of the right to life: the death penalty, abortion, and euthanasia. The contributors explore how young people understand and evaluate the right to life and its limitations. The book presents unique empirical research among today's youth and reveals that, among other concepts, religiosity matters. It provides insight into the acceptance, perception, and legitimation of human rights by people from different religious and cultural backgrounds. This investigation rigorously tests for inter-individual differences regarding political and judicial rights on religious grounds, while controlling for other characteristics. It will help readers better understand the many facets of this fundamental, yet controversial, philosophical question. The volume will be of interest to students, researchers, as well as general readers searching for answers.
Chapter 1. The right to life questioned. Introductory remarks (Hans-Georg Ziebertz) -- Chapter 2. Religion and the right to (dispose of) life. A study of the attitude of Christian, Muslim and Hindu students in India concerning death penalty, euthanasia and abortion (Francis-Vincent Anthony) -- Chapter 3. The Right to Life among Chilean Youth (Jorge Manzi) -- Chapter 4. Human dignity, religious ethics or hedonism - what predicts youth' attitudes in Germany towards the right to life in case of euthanasia and abortion? (Hans-Georg Ziebertz) -- Chapter 5. The impact of religion on attitudes towards abortion and euthanasia. An empirical study among Italian students (Francesco Zaccaria) -- Chapter 6. Religion, human rights and matters of life and death: Exploring attitude toward abortion and euthanasia among adolescents in England and Wales (Leslie J. Francis) -- Chapter 7. The Right to Life: A Perspective of Young Palestinian Muslims (Raymond J. Webb) -- Chapter 8. Attitudes toward Right to Life and Religiosity of Young People in Lithuania (Milda Ališauskienė) -- Chapter 9. Death penalty and the right to life. A comparative empirical study in Tanzania and Nigeria (Clement Fumbo) -- Chapter 10. Religion and attitudes towards abortion and euthanasia among young people in Poland and Norway (Pål Ketil Botvar) -- Chapter 11. Religion, trust in institutions and attitudes towards abortion: a comparison between Lutheran and Orthodox countries (Olga Breskaya).
Keywords: Human rights; Religion and sociology; Human Rights; Sociology of Religion